Bismuth trihalide based coordination polymers with the N‐donor cyanopyridine as source for charge transfer based luminescence - Borysova, Kateryna V.; Sorg, Jens R.; Mikhalyova, Elena A.; Oberst, Katharina; Würtele, Christian; Müller‐Buschbaum, Klaus (Zeitschrift für anorganische und allgemeine Chemie (1950), 2023)
Two one‐dimensional bismuth trihalide coordination polymers (CPs) [BiCl 3 ( 4‐cypy ) 2 ] n and BiBr 3 ( 4‐cypy ) 2 ] n were obtained by the solvent free melt approach in molten 4‐cyanopyridine under inert conditions and reduced pressure. The bismuth ions are surrounded by four halide atoms and two nitrogen atoms of the pyridyl ring of 4‐cypy in trans ‐mode. The polymeric linkage of both CPs is achieved by halide‐bismuth interactions while the 4‐cyanopyridine ligands show π ‐stacking interactions of their aromatic backbone. Both of compounds possess sufficiently intensive luminescence in the blue‐green region of the visible spectra upon cooling to 77 K following the trend of halide anion influence on the position of the emission band. Emission of these CPs arises from the contribution of two energy transfer mechanisms, MLCT from Bi 3+ to ligand and LMCT from ligand to Bi 3+ , respectively.